De la recherche de terrain sur la production agricole illégale de drogue - Pierre-Arnaud Chouvy (L'Espace Politique)
Explaining what are the practicalities and the stakes of conducting fieldwork on illegal drug crop production matters since it is only through fieldwork that empirical data can be gathered. It is all the more necessary since this kind of research is often hindered, often because of preconceived ideas, by the difficulties and dangers that are inherent to conducting fieldwork on illegal drug production. This text delves into the conduct of this type of fieldwork by focusing on what it implies in terms of preparation, access to the field, and research in the field, without denying what the hazards and risks are. It addresses the methodological issues, strategies and techniques, that allow to prepare and conduct such a research, down to the ethical imperatives of the post-fieldwork stages.